Simira cordifolia protects against metal induced-toxicity in Caenorhabditis elegans - Duran-Izquierdo, Margareth; Sierra-Marquez, Lucellys; Taboada-Alquerque, Maria; Olivero-Verbel, Jesus (Frontiers in Pharmacology, 2023)
Simira cordifolia (Hook.f.) Steyerm (Rubiaceae) is a vascular plant used in Northern Colombia as a source of pigments and wood. However, there is a lack of information regarding its pharmacology and toxicity. This research aimed to study the hydroalcoholic extract of S. cordifolia as a protector against metal-induced toxicity in Caenorhabditis elegans. Preliminary phytochemical screening of the hydroalcoholic extract of S. cordifolia (HAE-Sc) was conducted using HPLC-ESI-QTOF. Wild-type N2 C. elegans larvae were exposed to different concentrations of HAE-Sc evaluating lethality (50-5000 μg/mL), growth, lifespan, resistance to heat stress, and its protective effect against mercury (Hg)-, lead (Pb)-and cadmium (Cd)-induced lethality (50-1000 μg/mL). The main metabolites present in the extract were iridoids, β-carboline-alkaloids and polyphenols. Bioassays demonstrated that HAE-Sc exhibited low toxicity, with significant lethality (4.2 and 9.4%) occurring at 2500-5000 µg/mL. Growth inhibition reached up to 23.3%, while reproduction declined 13% and 17% at concentrations 500 and 1000 µg/mL, respectively. HAE-Sc enhanced the survival rate of the nematode under thermal stress by up to 79.8%, and extended the mean lifespan of worms by over 33% compared to control. The average lifespan was prolonged by 15.3 and 18.5% at 50 and 100 μg/mL HAE-Sc, respectively. The extract (1000 µg/mL) was able to reduce the death of C. elegans in the presence of heavy metals up to 65.9, 96.8 and 87% for Pb, Hg, and Cd, respectively. In summary, S. cordifolia shows potential protective effects in C. elegans against toxicity caused by heavy metals and heat.